Indicator values for food shelf life prediction: A review - Espinoza-Tellez, Teofilo (2024)
The short time that people have to cook their own food has led industries to satisfy the need for ready-to-eat products. This has motivated a progressive increase in studies that can determine the time at which the product can be safely consumed (shelf life). There are several methods for determining the shelf life of products; but regardless of the method used, the key is to know the minimum and/or maximum values of the indicators that define their deterioration. These values of spoilage indicators can change according to the compositional conditions of the food or the conditions under which it is stored during its shelf life. This review provides values for indicators used in tests for the determination of food shelf life, according to their nature, and environmental conditions, as way to be used by researchers as a reference in their predictions. The results of this research show scientific evidence through published articles about indicator values, their changes, referring to food shelf life kinetics. These values can be used for the prediction of food shelf life, for comparison purposes with their respective studies. It will be of importance for consumers, who will be able to use these values as a reference in the storage of these products. Shelf life indicator values for foods not considered in this work should be evaluated or experimented with in future work.